Identitas Nielsen - Triyanta Triyanta; Sutisna Sutisna (Institut Teknologi Bandung, 2001)
The gauge dependence of the effective action Γ that has been known for quite a long time is shown by a differential equation called the Nielsen identity. The identities appear in quantum field theory as due to the invariance of the Lagrange density with respect to the extended BRST transformations. In this paper the identities, both for the case of QED and QCD, will be derived in some gauge choices, first by following a method found in the references and second by a proposed method.